2019
DOI: 10.56093/ijas.v89i5.89662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus fertilization and microbial inoculants on yield, phosphorus use-efficiency and available phosphorus in maize (Zea mays)- wheat (Triticum aestivum) cropping system

Abstract: A field experiment was conducted between 2012-14 to investigate the effect of different phosphorus levels (control-no P, 33% P, 50% P, 100% P and 100% P in 3-splits of the recommended dose of P) and microbial inoculants (un-inoculated control, arbuscular mycorrhizal fungi, AM phosphate solubilising bacteria, PSB and AM+PSB) in maize-wheat system. The study revealed that the maize and wheat grain yields were increased by 20% and 40%, respectively, under 100% P which were significantly higher over control. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…In our study, the treatment showed a significant increase in AR S while an insignificant increase in AE S was observed. A similar effect on AE P and AR P in response to seed inoculation with microbial agents was recorded by Haokip et al [74]. Inoculation of maize seed with S-oxidizing bacteria and varied S sources resulted in a profound increase in S uptake [75].…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the treatment showed a significant increase in AR S while an insignificant increase in AE S was observed. A similar effect on AE P and AR P in response to seed inoculation with microbial agents was recorded by Haokip et al [74]. Inoculation of maize seed with S-oxidizing bacteria and varied S sources resulted in a profound increase in S uptake [75].…”
Section: Discussionsupporting
confidence: 79%
“…The increasing P integration rates stimulated root activity, nutrient absorption from the soil solution, and translocation from source to sink, indirectly influencing protein and amino acid levels (Kumar and Saini, 2022). Moreover, the abundant P supply may require the breakdown of carbohydrates into acetyl co-enzyme A, an essential component for the production of amino acids and proteins (Haokip et al, 2019;Ali et al, 2020). Thus, external application of P amplified the grain amino acids and net protein yield in our study.…”
Section: Figurementioning
confidence: 99%